The Effect of Using Wizard Liz’s Content on Students’ Listening Comprehension Skills at Ninth Grade Students of SMPN 1 Sepatan-Tangerang - Noer, Vanyssa Dwiana; arjulayana, Arjulayana; Anggraini, Diah Retno (Universitas Muhammadiyah Tangerang, 2025)
Listening comprehension is a crucial skill that significantly affects one's ability to communicate effectively in both professional and social contexts. To enhance students' listening abilities, many educators employ various methods and media, including utilizing YouTube videos from creators like The Wizard Liz. This research employed two types of assessments: a pre-test and a post-test. The study's participants were ninth-grade students from SMPN 1 Sepatan-Tangerang. Hypothesis testing was conducted using the Mann-Whitney test, where the null hypothesis (Ho) is rejected and the alternative hypothesis (H1) is accepted if the significance value is below 0.05. In the statistical analysis of Students' Listening skill results in the post-test, the value of Sig. (2-tailed) = 0.00 < 0.05 is obtained. Based on the data, it can be concluded that